Suicide by Homemade Hydrogen Sulfide in Turkey a Case Report - Uğur Koçak; Ahmet Hamdi Alpaslan; Murat Yağan; Erdal Özer (Adli Tıp Bülteni, 2016)
Suicide is a major public health problem and globally the second leading cause of death among young adults. Most of deaths due to H2S were seen among sewage or industrial workers because of acute exposure to this gas. Suicide by inhalation of homemade H2S has been reported for the first time in Japan, in 2007. In this study, for the first time, a 24-years-old male university student (from Turkey) preparing homemade H2S by using commercially available chemical products that were bought online in order to suicide was reported. The case is discussed in the light of related literature.